Captive-Versicherung im deutschen und US-amerikanischen Körperschaftssteuerrecht - Karl H. Bialek; Luc L. Grillet (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
This paper develops a positive framework for studying the deductibility of premiums paid to captive insurers as business expenses in German and American tax law. A systematic analysis of the legal rules and judicial Standards that have evolved during many years of corporate litigation and quarelling with the Internal Revenue Service is compared with the economic viability of captive insurance as a risk-transfer instrument. The analysis concludes that sound public policy requires tax deductions for commercial and captive insurance premiums to be treated equally if they are actuarially justified.
Keywords: 330